Additive manufacturing as smart manufacturing system for fabrication of interference screw - Lusia Permata Sari HARTANTI; Paulus Wisnu ANGGORO; Rifky ISMAIL; Jamari JAMARI; Athanasius Priharyoto BAYUSENO (Journal of Advanced Mechanical Design, Systems, and Manufacturing)
Smart additive manufacturing (AM) is a complex process that integrates several digital technologies in design, planning, manufacturing, control, and services to make them more responsive and adaptable. Smart AM has demonstrated the ability to provide excellent digital technology for implant, tissue, or organ printing in the medical field. An anterior cruciate ligament (ACL) tear is an injury that occurs during strenuous physical activity. One of the implants utilized in ACL reconstruction is an interference screw. The polymers used to make an interference screw for ACL surgery are typically bioresorbable polylactic acid (PLA). Investigations on the effects of process parameters such as nozzle diameter and printing speed parameters on interference screw printing properties at 90° build orientation are still limited. Smart AM technology-related materials and processes are the primary areas of this study. This study evaluated the effects of printing speed and nozzle diameter settings, as well as the mechanical, biological, and physical characteristics of PLA interference screws printed at a 90° build orientation. The interference screws were 3D printed using material extrusion-based AM. The dimension deviation was 0.04 to 0.33%, and the density was 1.1 to 1.25 g/cm3. The A, B, and C interference screws were torque tested for all in a good clamping area, while the D-interference screw was in a clamping area. The weight loss of the interference screws in the biodegradation profile decreased after five weeks. The optimal process parameters were 50 mm/s printing speed and 0.3 mm nozzle diameter. The findings contribute to the production strategy of 3D-printed interference screw-based polymeric materials. It can be helpful to understand how different manufacturing parameters function and how those parameters affect the quality of the final product.